The Pengaruh Berbagai Macam Suhu dalam Pembuatan Gula Cetak Dari Nira Aren (Arenga pinnata (Wurmb.) - Hadi, Samsul; Setiawan, Deni; Nastiti, Kunti (Nusantara Journal of Science and Technology, 2024)
Palm sugar consumption levels may vary depending on societal habits and individual preferences. Palm sugar is a natural sweetener that comes from sap or water with a brownish color. However, the color of palm sugar varies from light to dark brown. So the aim of this research is to regulate the temperature for making sap sugar to prevent the formation of a brown color in making sugar. The method used in making sap sugar is setting various temperatures, to get a brighter color than the control with the help of spectrophotometry at a wavelength of 420 nm. The results in this study are absorbance data at each temperature, namely 1000C: 0.832 ± 0.023; 900C: 0.821 ± 0.051; 800C: 0.799 ± 0.012; 700C: 0.671 ± 0.027; 600C: 0.621 ± 0.034. Based on statistical analysis at temperatures of 700C and 600C it can significantly reduce the color intensity on spectrophotometer examination. The conclusion is that the appropriate temperature for processing sap sugar to reduce color intensity is 700C and 60 0C.